Persepsi Masyarakat Dusun Tahoku Desa Hila Atas Status Anak di Luar Nikah di Kaji Dalam Perspektif Hukum Islam - Muhaemin Waliyudin; Jumiati Tuharea; Laros Tuhuteru (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research is a qualitative descriptive study, namely research that intends to understand the phenomena of what is experienced by the research subjects, for example behavior, perceptions, motivations, actions, and so on. Islamic law and the efforts of religious leaders, traditional leaders and community leaders in preventing cases of children out of wedlock. This research was conducted in Tahoku Hamlet, Hila Village, Leihitu District, Central Maluku Regency. Data collection was carried out through interviews with Several Actors and Religious Leaders, Traditional Leaders and Community Leaders as resource persons who are considered to have an important role in life in society. The results and this research are the views of the community towards children out of wedlock and Islamic law, namely the community has a view that refers to the opinions of scholars who allow in Islamic law so that if there are pregnant women outside of marriage, they should be married off as soon as possible so that they can save their child's status as a legitimate child. as well as having good prejudice for the benefit of the people in order to continue to attribute the lineage, as well as the rights of guardians and inheritance to him. The efforts of religious leaders, traditional leaders and community leaders agreed to prevent cases of children outside marriage in Tahoku Hamlet in collaboration with related parties, namely KUA in providing counseling so that they can provide legal education to the community and religious leaders. Families in fostering children make rules and sanctions on issues of night time out so as not to cause excessive rejuvenation and special social sanctions as a deterrent effect for their children so as to prevent adolescent associations